2018
DOI: 10.13075/mp.5893.00717
|View full text |Cite
|
Sign up to set email alerts
|

The usefulness of bronchial challenge tests in the diagnosis of occupational asthma

Abstract: Bronchial hyperresponsiveness (BHR) is the individual ability to respond with bronchoconstriction to a variety of specific and nonspecific stimuli which do not cause these symptoms among healthy subjects. Bronchial hyperresponsiveness is one of the hallmark features of asthma. The degree of bronchial hyperresponsiveness is variable among individuals with asthma and may correlate to its severity (the more severe asthma the higher bronchial hyperreactivity). Bronchial hyperresponsiveness is evaluated by performi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
(129 reference statements)
0
1
0
Order By: Relevance
“…Mounting studies have demonstrated that bronchial provocation test (BPT) played an important role in diagnosing asthma [11,12]. In clinical application, BPT is severed as the gold standard of asthma, especially cough variant asthma (CVA).…”
Section: Introductionmentioning
confidence: 99%
“…Mounting studies have demonstrated that bronchial provocation test (BPT) played an important role in diagnosing asthma [11,12]. In clinical application, BPT is severed as the gold standard of asthma, especially cough variant asthma (CVA).…”
Section: Introductionmentioning
confidence: 99%